PEMBELAJARAN BERBASIS SCL BAGI PESERTA DIDIK DALAM MENJAWAB SOAL TEKS BAHASA INGGRIS PADA PAKET B DAN C DI LEMBAGA PEMBINA KHUSUS ANAK KOTA KUPANG - Sogen, Yosephina Katharina; Syukur, Abdul; Simbolon, Gallex (Nusa Cendana University, 2021)
The lessons for Adult Education (B and C Package) at the juvenile penitentiary are learning that is equivalent to the teaching and learning process in formal schools. B Package is equivalent to Junior High School and C Package is equivalent to Senior High School. Learning activities in class for students need to be changed so that student participation is very important in understanding and answering the reading comprehension. Exercises in reading texts and answering the questions correctly are activities that can increase student activity and participation. Students work on the questions by reading and translating difficult words in the reading so that they can be understood and help students answer questions according to the content of the reading. Students also study and discuss in groups of 5 student and discuss together to answer questions. The discussions that were carried out were successful in making students understand the material and be able to work or answer questions in English properly and correctly. Students can learn from their own friends and understand better if their friends explain so that it can increase motivation in learning. The learning activities of B and C Package's students more active. The students have the opportunity to learn from each other and with simple language, difficult English materials can be worked out well. Problem-based learning is one part of student- learning problem but it cannot increase activeness and participation and is unable to solve learning problems in class, so a change in the learning model is made, namely the small group discussion. The Small Group Discussion model was used in learning at LPKA Penfui Kupang.